Persepsi Siswa SMA Negeri 13 Medan tentang Kasus Ayah Bunuh 4 Anak di Jakarta Selatan - Lubis, Vidia Zahra (KESKAP: Jurnal Kesejahteraan Sosial, Komunikasi dan Administrasi Publik, 2024)
News of a murder is an incident or event that takes someone's life intentionally or not, which is monitored by media crews who immediately go out into the field to carry out coverage which is then informed to the wider public. This research discusses and explains the perceptions of students at SMA Negeri 13 Medan regarding the case of a father who killed 4 children in South Jakarta. This research aims to determine the perceptions of SMAN 13 Medan students regarding the case of a father killing 4 children in South Jakarta. This research uses qualitative methods with a qualitative descriptive study research approach. The data collection process was obtained through in-depth interviews and observations of informants. Data sources were collected using interview and documentation techniques. Then the data collected was analyzed using qualitative descriptive methods. The research results show that the role of parents in protecting children from violence is very important, parents must build open communication to avoid similar cases of violence in the future